2016
DOI: 10.1186/s12969-016-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

Behçet’s disease in children, an overview

Abstract: SummaryBD is a systemic inflammatory disease with a variable vasculitis. Paediatric onset is very rare and carries a strong genetic component. Oral ulcers and fever of unknown origin are frequent at onset and difficult to distinguish from other inflammatory disorders; therefore, expert opinion is still mandatory to recognize the disease early. An international expert consensus has recently proposed new classification criteria for children with BD. The clinical spectrum of BD is heterogeneous and influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
110
0
17

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 61 publications
2
110
0
17
Order By: Relevance
“…However, in few series, it was reported that 3.3 and 26% of the patients with BD were juvenile-onset BD [2]. The clinical symptoms are not diferent from adults but the diagnosis may be delayed in pediatric patients because of mild symptoms [2]. Juvenile onset patients had more familial cases compared with adult-onset patients [39].…”
Section: Age and Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…However, in few series, it was reported that 3.3 and 26% of the patients with BD were juvenile-onset BD [2]. The clinical symptoms are not diferent from adults but the diagnosis may be delayed in pediatric patients because of mild symptoms [2]. Juvenile onset patients had more familial cases compared with adult-onset patients [39].…”
Section: Age and Gendermentioning
confidence: 99%
“…The prevalence of juvenile BD is unknown. However, in few series, it was reported that 3.3 and 26% of the patients with BD were juvenile-onset BD [2]. The clinical symptoms are not diferent from adults but the diagnosis may be delayed in pediatric patients because of mild symptoms [2].…”
Section: Age and Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…BD is rare in paediatric age and the prevalence is unknown. It is difficult to make diagnosis under 16 years due to the heterogeneous clinical picture, such as oral and genital ulcers, erythema nodosum, superficial thrombophlebitis, acne and arthritis [6, 7]. Factors that contribute to the pathogenesis of BD include the host’s genetic profile and immune system, and environmental factors such as the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of juvenile BD is unknown. But in few series, it is reported between 3, 3 and 26% of BD patients were before age of 16 years [10]. BD affects the both gender equally [11].…”
mentioning
confidence: 99%